COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF THE LQ-45 COMPANY BEFORE AND AFTER THE ENACTMENT OF UNDANG-UNDANG NO. 36 TAHUN 2008 - Pramita, Nilam Sari; Rusydi, M. Khoiru (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The Indonesian government has made legislative changes in 2008 in the field of taxation related to income tax rate changes in individual taxpayers and corporate taxpayers. The changes in tax rates expected to impact the company's financial performance. Financial performance indicators used in this study are part of the financial ratios, namely current ratio, debt to equity, leverage ratio, gross profit margin, operating profit margin, net profit margin, inventory turnover, total asset turnover, return on invesment, and return on equity. This study aims to analyze and provide empirical evidence of whether there are differences in financial performance between periods before and after the change in tax rates. The populations in this study are the companies LQ-45 as of August 2011. The research data sample consists of 22 companies listed in Indonesia Stock Exchange with sampling through judgment sampling technique. In this study used four years of research, namely in 2007, 2008, 2010, and 2011. The periods before the enactment of Tax Law Number 36 of 2008 are 2007 and 2008, while the periods after the enactment of Tax Law Number 36 of 2008 are 2010 and 2011. The data used in this study is secondary data, the financial data in the form of the company's annual financial reports as sample of research. The results showed that there is empirical evidence to show significant differences in the variables current ratio, debt to equity, and total asset turnover in the period after the changes in tax rates. The author suggests the need for further research with using a larger sample in order to obtain results more specific analysis. In addition, the use of indicators of financial performance besides the financial ratios should be considered in future studies. Keywords: income tax company, financial performance, financial ratio